Sustainable Green Practice in SMEs – An Examination of VBN Framework for Improving Productivity - Yacob, Peter; Jaganathan, Mathivannan; Ishak, Khairol Anuar; Khor, Saw Chin; Maludin, Nurliyana; Mohd Zin, Adi Wira; Nodesan, Suresh (International Journal of Supply Chain Management, 2019)
The last few years have seen an exponential increase in the significance of the environmental agenda at the global level. Despite decades of research, the motivations that drive managers to engage in sustainable green practices remained uncertain. This study examines the degree to which value-belief-norm framework in explaining engagement in sustainable green practices. The data for this study was collected from 260 manufacturing SMEs and was analyzed by employing Structural Equation Modelling. The results indicated that environmental beliefs have a significant positive effect on SME's sustainable green practices, but these effects have not been demonstrated by environmental norms and environmental values. In view of these results, the findings have both policy and education implications as it is believed that a behaviour which encourages manufacturing SMEs to adopt green practices with respect to environmental concerns.